2021
DOI: 10.1038/s41467-021-24419-8
|View full text |Cite|
|
Sign up to set email alerts
|

Fingerprinting the Cretaceous-Paleogene boundary impact with Zn isotopes

Abstract: Numerous geochemical anomalies exist at the K-Pg boundary that indicate the addition of extraterrestrial materials; however, none fingerprint volatilization, a key process that occurs during large bolide impacts. Stable Zn isotopes are an exceptional indicator of volatility-related processes, where partial vaporization of Zn leaves the residuum enriched in its heavy isotopes. Here, we present Zn isotope data for sedimentary rock layers of the K-Pg boundary, which display heavier Zn isotope compositions and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The empirical factor a for tektite data (0.999 to 0.9997) based on the Zn isotope ratio data determined for distal K-Pg boundary sites (Mathur et al, 2021), and the data collected in this work imply Zn isotopic fractionation from volatilization below that expected by theoretical Rayleigh distillation to vacuum (a % 0.985 in a vacuum). In all cases, the lower a is likely attributable to effects linked to diffusion in the thin layer of the ejecta, slowing down the evaporation (Moynier et al, 2009; and/or suppression of Zn isotopic fractionation during large-scale evaporation under high pressure (i.e., non-vacuum) conditions (Davis and Richter, 2014;Day et al, 2017;Wimpenny et al, 2019;Chernonozhkin et al, 2021).…”
Section: Potential Traces Of Impact Volatilizationmentioning
confidence: 52%
See 4 more Smart Citations
“…The empirical factor a for tektite data (0.999 to 0.9997) based on the Zn isotope ratio data determined for distal K-Pg boundary sites (Mathur et al, 2021), and the data collected in this work imply Zn isotopic fractionation from volatilization below that expected by theoretical Rayleigh distillation to vacuum (a % 0.985 in a vacuum). In all cases, the lower a is likely attributable to effects linked to diffusion in the thin layer of the ejecta, slowing down the evaporation (Moynier et al, 2009; and/or suppression of Zn isotopic fractionation during large-scale evaporation under high pressure (i.e., non-vacuum) conditions (Davis and Richter, 2014;Day et al, 2017;Wimpenny et al, 2019;Chernonozhkin et al, 2021).…”
Section: Potential Traces Of Impact Volatilizationmentioning
confidence: 52%
“…This trend may suggest that the Zn isotope ratios for the upper sections of the drill core may have retained a hint of volatility-driven isotopic fractionation. While one should keep in mind that seawater nodules, tracing seawater Zn isotope ratios, can also display higher d 66/64 Zn values (Maréchal et al, 2000), the trends for K-Pg boundary sediments highlighted by Mathur et al (2021) are observed for both marine and terrestrial sites, confirming the robustness of Zn isotope systematics. In addition, no Zn carrier phases were identified in the Paleogene sediments and transitional unit samples studied here.…”
Section: Potential Traces Of Impact Volatilizationmentioning
confidence: 60%
See 3 more Smart Citations